Reprobation and God's sovereignty: recovering a Biblical doctrine - Sammons, Peter (Kregel Publications, 2022)
God's right to judge humanity is written on the very fabric of human existence The doctrine of reprobation--that is, the eternal, unconditional decree of God for the non-elect--is frequently misconstrued in both pastoral and theological literature.